a(x-y)-b(x-y)

asked by guest
on Mar 24, 2025 at 10:31 pm



You asked:

Evaluate the expression: a(xy)b(xy)a\left( x - y \right) - b\left( x - y \right)

MathBot Answer:

Evaluated



a(xy)b(xy)=a(xy)b(xy)\displaystyle a\left( x - y \right) - b\left( x - y \right) = a \left(x - y\right) - b \left(x - y\right)


Expanded

a(xy)b(xy)=xaxbya+yba\left( x - y \right) - b\left( x - y \right) = x a - x b - y a + y b


Factored

a(xy)b(xy)=(xy)(ab)a\left( x - y \right) - b\left( x - y \right) = \left(x - y\right) \left(a - b\right)